Fabrication of Au-In2O3 Thin/Thick-Film Gas Sensors and Their Sensing Characteristics for Toxic Gases - Kim, Inho; Park, Eun Duck; Kim, Han Soo; Han, Sang Do (Journal of Sensor Science and Technology, 2024)
This paper reports on highly sensitive and selective Au-In2O3 thin-and thick film gas sensors for detecting and measuring toxic gases. The used thin film was deposited on an alumina substrate using a high-frequency sputtering method, the sensor substrate with platinum heater and gold electrode was formed by screen printing, and the nano-catalyst material Au was deposited by thermal vapor deposition. The thick-film gas sensor was fabricated by screen printing using Au-In2O3 paste, and the sensor was finalized by annealing in air at 800oC. The target toxic gases used were acetaldehyde, dimethyl disulfide, and 2-methyl-1-propanol. The fabricated thin-film gas sensors showed excellent sensitivity to dimethyl disulfide, and the thick-film gas sensors showed a strong response to acetaldehyde. In particular, the thin-film sensors annealed at 800oC exhibited excellent sensing characteristics such as high sensitivity, fast recovery, stability, and linearity. Based on the surface oxidation reaction and electron transfer mechanism of the Au-In2O3 system, a sensing reaction mechanism and surface energy band model for 2-methyl-1-propanol were proposed.
Keywords: Au-In2O3; Gas sensor; Sputtering; Thermal evaporation; Thin-thick film; Toxic gas